Sistem Perbandingan Pendidikan Negara India dengan Sistem Pendidikan di Negara Jepang - Nur Salwa Harahap; Mislaini Mislaini; Elvira Darmawanti (Universitas Palangka Raya, 2025)
This article discusses a comparison of the educational systems between Japan and India, two countries with rich and diverse educational traditions. The Japanese education system is known for its systematic and structured approach, emphasizing discipline, hard work and quality-based learning, whereas India has a more heterogeneous system, influenced by broader social and economic diversity. In Japan, primary and secondary education are very important stages, with a focus on moral and academic development. In contrast, India's education system faces major challenges related to infrastructure, access, and inequality between urban and rural areas. This article also reviews recent education policies in both countries, as well as their efforts to reform higher education and align curricula with global needs. Through this analysis, it is hoped that it can provide deeper insight into the strengths and weaknesses of each country's education system, as well as lessons that can be taken to improve the overall quality of education.